Isotopic and elemental determination of lead in particulate matter in the cities of Goiânia (GO) and Rio Claro (SP) using ICP-MS technique - Gemeiner, Hendryk [UNESP] (2016)
The toxic metal lead (Pb) can be harmful to human health in various manners, but is also considered as a distinguished tracer of environmental pollution, since the relative abundance of its four stable isotopes with the atomic masses of 204, 206, 207 and 208 varies with the emission source. This study is focused on the lead concentrations and isotope ratios in the particulate matter of the Brazilian cities of Goiânia (GO) and Rio Claro (SP), in order to determine the main Pb pollution sources. Particulate matter samples were collected on clean Teflon filters during the rainy and dry season between 2014 and 2016 on the campus of the State University of São Paulo (UNESP) in Rio Claro city and in the centre of Goiânia city near main roads with a high traffic volume. The Pb concentrations as well as the 206Pb/207Pb and 208Pb/207Pb stable isotope ratios of the particulate matter samples were analysed by Inductively-Coupled Plasma Mass Spectrometry. To apply this analytical technique successfully, it was necessary to optimize parameters in case of acquisition time, detector dead time and mass discrimination, which affect the measurement accuracy and precision. Results showed that lead concentrations in Goiânia were different between rainy and dry season. In Goiânia, Pb concentrations showed higher values in dry season than in rainy season, while Pb concentrations were more similar in both sampling periods in Rio Claro. Back trajectories were analysed with the HYSPLIT model to investigate associations between Pb concentration levels and the direction of incoming air masses. However, the comparison of the obtained 206Pb/207Pb and 208Pb/207Pb isotope ratios data with data of potential Pb sources from previous studies indicated that gasoline may be considered as main Pb sources in the particulate matter of Goiânia and Rio Claro. Pb isotope ratios in Goiania were slightly different between dry and rainy season, while in Rio Claro, 206Pb/207Pb isotope ratios showed markedly higher values in dry season than in rainy season. Hence, Pb in Rio Claro in dry season also seems to be influenced by industrial emissions. These assumptions were supported by the calculation of 208Pb/206Pb-207Pb/206Pb diagrams and the contribution factor of Pb coming from gasoline by applying binary mixing equations.